Gallbladder adenocarcinoma with sarcoid-like reaction in regional lymph nodes: report of a case - Kawasaki, Yota (BMC Cancer, 2014)
BACKGROUND: Sarcoid-like reaction is often seen in various types of carcinoma, not only in the primary tumor, but also in regional lymph nodes, and can occur at any time, not only at the time of diagnosis, but also after treatment. However, few cases of hepatopancreatobiliary carcinoma, and no cases of gallbladder cancer with sarcoid-like reaction involving the lymph nodes have been described. This report is the first report of a sarcoid-like reaction involving the lymph nodes in a case of gallbladder cancer. CASE PRESENTATION: We encountered a rare case of gall bladder cancer with sarcoid-like reaction in the lymph nodes. Since regional lymph node swelling that was difficult to differentiate from metastasis was found preoperatively, swollen nodes were examined histologically using frozen sections. Based on this histology, the swollen nodes were diagnosed as showing sarcoid reaction and therefore extended lymphadenectomy was avoided. The patient did not receive any adjuvant chemotherapy and has shown no recurrence of disease as of 4 years after surgery. CONCLUSION: Distinguishing between metastasis and sarcoid-like reaction in lymph nodes by preoperative imaging is still difficult. The present case shows that it is important to histologically examine swollen nodes by biopsy or by sampling before deciding on the treatment strategy for gall bladder cancer with swollen lymph nodes.